Scoping Review: Pengaruh Diabetes Mellitus terhadap Tingkat Keparahan Gangguan Pernapasan pada Pasien COVID-19 - Annisa Maulidianti; Nuzirwan Acang; Eka Hendryanny (Bandung Conference Series: Medical Science, 2022)
Abstract. Coronavirus Disease 2019 (COVID-19) is an infectious disease that attacks the respiratory tract, with a causative cause, namely the SARS-Cov-2 virus. Respiratory disorders that occur vary from mild, moderate, severe to critical. Some of the patients requiring intensive care at the hospital were COVID-19 patients who were found to have a comorbid condition of diabetes mellitus. Based on this phenomenon, the problem in this study is, Does diabetes mellitus have an influence on the severity of respiratory disorders in COVID-19 patients? The study was conducted using a scoping review method with a sample of international scientific articles that meet the eligibility criteria (eligible). The results in this study were taken from 3 databases, namely Springer Link, Science Direct, and Pubmed with initial search results there were 525 articles and eight articles that met the eligibility (eligible). Selected based on PICOS. The results of the scoping review show that COVID-19 patients with diabetes mellitus have a tendency to develop a severe respiratory disorder characterized by bilateral infiltrated lung lesions, severe pneumonia, the incidence of ARDS, and the high use of invasive ventilation in supportive therapy for COVID-19 patients with diabetes mellitus. This is related to the dysregulation of the innate and adaptive immune systems, increased pro-inflammatory cytokines, and high levels of ACE-2 in diabetes mellitus patients. Thus, it can be concluded from this study that there is an influence between diabetes mellitus and the severity of respiratory disorders in COVID-19 patients. Abstrak. Coronavirus Disease 2019 (COVID-19) adalah penyakit infeksi yang menyerang saluran pernapasan dan disebabkan oleh virus SARS-Cov-2. Gangguan pernapasan yang terjadi bervariasi, antara lain gangguan pernapasan ringan, sedang, berat hingga kritis. Sebagian besar pasien yang membutuhkan perawatan intensif di rumah sakit merupakan pasien COVID-19 yang memiliki komorbid diabetes mellitus. Berdasarkan fenomena tersebut maka permasalahan dalam penelitian ini adalah, Apakah diabetes mellitus memiliki pengaruh terhadap tingkat keparahan gangguan pernapasan pada pasien COVID-19? Penelitian dilakukan dengan metode scoping review, sampel yang digunakan adalah artikel ilmiah internasional yang memenuhi kriteria kelayakan (elegible). Hasil penelitian ini diambil dari 3 database yaitu Springer Link, Science Direct dan Pubmed dengan pencarian awal terdapat 525 artikel dan kemudian diseleksi berdasarkan PICOS. Artikel yang memenuhi kelayakan (elegible) berjumlah delapan artikel. Hasil scoping review menunjukkan pasien COVID-19 dengan diabetes mellitus memiliki kecenderungan mengalami gangguan pernapasan berat yang dikarakteristikkan dengan adanya lesi paru infiltrat bilateral, pneumonia berat, komplikasi ARDS dan tingginya penggunaan ventilasi invasif pada terapi supportif. Hal tersebut terkait dengan adanya disregulasi sistem imun innate dan adaptif, peningkatan sitokin pro-inflamasi dan jumlah ACE-2 yang tinggi pada pasien dengan diabetes mellitus. Simpulan penelitian ini terdapat pengaruh diabetes mellitus terhadap tingkat keparahan gangguan pernapasan pada pasien COVID-19.